Sun Circle - Gunn N. M. Neil M. (Edinburgh, Canongate Classics, 2001)
First published in 1933, this is Breetas story of love and awakening, set in the very early history of Scotland: Breetas people are the ancient, newly Christianized Pictish tribes living in remote Northern Scotland in the 9th century. They are assailed by the pagan Vikings from across the sea.